Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/1071676
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Cytotoxic Effects of Moringa oleifera (Moringa) and Azadirachta indica (Neem) Methanolic Extracts against Strains of Enterococcus faecalis

Abstract: Objective To evaluate antibacterial and cytotoxic effect of 2 methanolic extracts of Azadirachta indica and Moringa oleifera against strains of Enterococcus faecalis (ATCC 29212) in vitro. Methods The methanolic extracts of Azadirachta indica and Moringa oleifera were prepared in vitro. The antibacterial effect of the extracts against Enterococcus faecalis was evaluated using the agar diffusion technique. The minimum inhibitory concentration (MIC) was determined using the microdilution method and the cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 22 publications
3
28
0
3
Order By: Relevance
“…Many studies have shown that the leaf, flower, bark, root, seed and nearly all types of MO tissues exhibit antimicrobial activity against several pathogens such as Vibrio cholerae and Escherichia coli and also viruses, fungi and parasites [10][11][12]. However, it is difficult to find in the literature, which methodologies are effective for antimicrobial purposes and for which pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the leaf, flower, bark, root, seed and nearly all types of MO tissues exhibit antimicrobial activity against several pathogens such as Vibrio cholerae and Escherichia coli and also viruses, fungi and parasites [10][11][12]. However, it is difficult to find in the literature, which methodologies are effective for antimicrobial purposes and for which pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…All parts of the plant can be utilized by humans [8]. Various reviews noted antioxidant, antimicrobial, anti-inflammatory, anticancer, analgesic, cardiovascular, antiulcer, immunomodulation, antihypertensive, hepatoprotective, diuretic, antiurolithiatic, anthelmintic, hypoglycemic, antidiabetic, anti-asthmatic, and antiaging potentials of the plant [1,[9][10][11][12][13][14][15][16][17]. Its benefits in nutritional value present higher standard in dietary intake than is recommended by the WHO [5].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial effect of M. oleifera is due to the chemicalcompound4-(4'-O-acetyl-α-L-rhamnopyranosyloxy) benzylisothiocyanate,whose mechanism of action involves inhibition of essential cellular membrane enzymes [17].…”
Section: Discussion:-mentioning
confidence: 99%